The last murder at the end of the world eaudiobook A novel. - Turton, Stuart (Tantor Media, 2024)
Solve the murder to save what's left of the world. Outside the island there is nothing: the world was destroyed by a fog that swept the planet, killing anyone it touched. On the island: it is idyllic. One hundred and twenty-two villagers and three scientists, living in peaceful harmony. The villagers are content to fish, farm and feast, to obey their nightly curfew, to do what they're told by the scientists. Until, to the horror of the islanders, one of their beloved scientists is found brutally stabbed to death. And then they learn that the murder has triggered a lowering of the security system around the island, the only thing that was keeping the fog at bay. If the murder isn't solved within ninety-two hours, the fog will smother the island—and everyone on it. But the security system has also wiped everyone's memories of exactly what happened the night before, which means that someone on the island is a murderer—and they don't even know it. And the clock is ticking.